Topology Detection for Output-Coupling Weighted Complex Dynamical Networks with Coupling and Transmission Delays. (31st July 2017) - Wang, Xinwei; Jiang, Guo-Ping; Fan, Chunxia; Wu, Xu
Abstract : Topology detection for output-coupling weighted complex dynamical networks with two types of time delays is investigated in this paper. Different from existing literatures, coupling delay and transmission delay are simultaneously taken into account in the output-coupling network. Based on the idea of the state observer, we build the drive-response system and apply LaSalle's invariance principle to the error dynamical system of the drive-response system. Several convergent criteria are deduced in the form of algebraic inequalities. Some numerical simulations for the complex dynamical network, with node dynamics being chaotic, are given to verify the effectiveness of the proposed scheme.